Assessing the effectiveness of state-level pharmacy laws on opioid prescribing practices - Shrivastava, Pranjul; Syed Sabir Ali, Syed Sajid Ali (Journal of Neonatal Surgery, 2025)
Despite their positive impacts on health, medications can have negative side effects because of adverse drug reactions (ADRs). Physicians, pharmacists, and nursing staff have a duty to use caution while prescribing medication. Patients are becoming more conscious of drug-related issues in today's consumer-driven world, and they want to be included in the decision-making process for many elements of their prescription and health care. This study concludes that polypharmacy, a history of bad drug responses, and coexisting illnesses are independent predictors of adverse drug reactions. Elderly people are more susceptible to adverse drug reactions due to comorbidity and a higher number of medications. Although not statistically significant, this study indicated that male gender, age, and comorbidity are associated with a higher risk of adverse drug responses (ADRs). It also implies that more research is necessary to determine whether there is a clear link between male sex and adverse drug reactions. The most important and noteworthy stage in drug safety is adverse drug reaction monitoring, which lowers the morbidity and death associated with ADRs. When prescription medication, especially to vulnerable age groups, healthcare providers should be more aware of adverse drug reactions (ADRs) and take all factors into account.